PERANCANGAN TOPOLOGI JARINGAN DAN VIRTUALISASI SERVER DI UT SCHOOL DENGAN VMWARE VSPHERE - Muhammad Afif Affandi; Zuliadi Prabowo (Universitas Diponegoro, 2025)
The digitization process carried out by UT School requires storage media that can be accessed by many people, namely servers. Currently UT School has a local server that is used for applications and data storage. But the local server can only be accessed by the UT School Head Office in Jakarta. This research aims to create a virtualized server that can be accessed via Public IP, so that UT School can optimally utilize the existing local server. The research method used is the experimental design method with supporting data sourced from UT School. In testing the performance of VM 1 services using the Microsoft Windows Server 2016 operating system, the resulting Total Number of Clicks is 3160 with 0 Errors, All Times Spent 119,373,856 ms and Average Click Time of all URLs is 4,625 ms. Meanwhile, on VM 2 using the Linux Ubuntu Server 18.04 operating system, the resulting Total Number of Clicks is 45,897 with 0 Errors, All Times Spent 121,220,577 ms and Average Click Time of all URLs is 2,692 ms. When testing the utilization rate of VM 1 on the CPU increased by 99% and in memory experienced an increase in utilization by 26%. While the utilization rate of VM 2 has increased by 40.23% and in memory has increased utilization by 10%. Keywords: server, server virtualization, service performance, utilization rate